2018
DOI: 10.1002/jccs.201800128
|View full text |Cite
|
Sign up to set email alerts
|

Structure investigation, spectral characterization, electronic properties, and antimicrobial and molecular docking studies of 3′‐(1‐benzyl‐5‐methyl‐1H‐1,2,3‐triazole‐4‐carbonyl)‐1′‐methyl‐4′‐phenyl‐2H‐spiro[acenaphthylene‐1,2′‐pyrrolidine]‐2‐one

Abstract: A new compound, 3′‐(1‐benzyl‐5‐methyl‐1H‐1,2,3‐triazole‐4‐carbonyl)‐1′‐methyl‐4′‐phenyl‐2H‐spiro[acenaphthylene‐1,2′‐pyrrolidin]‐2‐one (BTANP), was prepared, analyzed by Single Crystal X‐ray Diffraction (SCXRD), and investigated spectroscopically, which includes NMR, FT‐IR/Raman, UV–Vis, and fluorescence studies. All the computations have been made with the resource of density functional theory (DFT) (B3LYP/6‐311G [d,p]) and compared with the measured values. The vibrational assignments with potential energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In 2019, Malarkodi et al [10] synthesized and compared 3'- (1benzyl-5-methyl-1H-1,2,3-triazole-4carbonyl)-1'methyl-4'-phenyl-2H-spiro[acenaphthylene-1,2'-pyrrolidin]-2-one (BTANP) against a few bacterial and fungal strains as well as standard drugs. In addition, molecular docking mockups were developed on BTANP against topoisomerase II gyrase and human lanosterol 14 α demethylase enzymes [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Malarkodi et al [10] synthesized and compared 3'- (1benzyl-5-methyl-1H-1,2,3-triazole-4carbonyl)-1'methyl-4'-phenyl-2H-spiro[acenaphthylene-1,2'-pyrrolidin]-2-one (BTANP) against a few bacterial and fungal strains as well as standard drugs. In addition, molecular docking mockups were developed on BTANP against topoisomerase II gyrase and human lanosterol 14 α demethylase enzymes [10].…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Rajeswari et al [9] developed an efficient, onepot, four-component condensation procedure for the synthesis of selective spirooxindolepyrrolizine-linked 1,2,3-triazole conjugates via a [3+2] cycloaddition (32CA) reaction using coumarin-3-carboxylic acid, N-propargylated isatin, L-proline/sarcosine, and aryl azides and using Cu(I) as a catalyst in the presence of glacial CH 3 COOH at 60 • C [9]. In 2019, Malarkodi et al [10] synthesized and compared 3'-(1-benzyl-5-methyl-1H-1,2,3-triazole-4carbonyl)-1'methyl-4'-phenyl-2H-spiro[acenaphthylene-1,2'-pyrrolidin]-2-one (BTANP) against a few bacterial and fungal strains as well as standard drugs. In addition, molecular docking mockups were developed on BTANP against topoisomerase II gyrase and human lanosterol 14 α demethylase enzymes [10].…”
Section: Introductionmentioning
confidence: 99%
“…In triazole rings, the bond distances and bond angles of molecules A & B are found nearer to the reported values for analogous triazole derivatives. [ 40 , 41 ] The selected geometric parameters are provided in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they measured the hardness (η = 0.999), chemical potential (μ = −7.026), electronegativity (χ = 7.026), and electrophilicity index (ω = 24.707). Malarkodi et al 20 have analyzed the FMO characteristics of 3′-(1-benzyl-5-methyl-1 H -1,2,3-triazole-4-carbonyl)-1′-methyl-4′-phenyl-2 H -spiro-[acenaphthylene-1,2′-pyrrolidine]-2-one using DFT (B3LYP) with the 6-311G(d,p) basis set. They have found that this molecule has a small HOMO–LUMO energy gap of −3.4869 eV with large intramolecular charge transfer interactions, and therefore it is classified as a soft, highly polarizable, and reactive molecule.…”
Section: Introductionmentioning
confidence: 99%